Tris(4-tert-butylphenyl)phosphine oxide - Hao, Yin-Ge (International Union of Crystallography, 2009)
In the title compound, C(30)H(39)OP, the P=O bond length is 1.4866 (12) Å and the P—C bond lengths range from 1.804 (2) to 1.808 (13) Å. The molecle is located on a crystallographic mirror plane. The methyl groups of one tert-butyl group are disordered over two sites in a 0.776 (4):0.224 (4) ratio.